Pengaruh Media Smart Box terhadap Hasil Belajar dan Minat Belajar pada Mata Pelajaran Pendidikan Pancasila Kelas III MI Raudlatul Muta’alimin - Siti Halimatus Sa'diyah; Sirojuddin Abror; M Yusron Maulana El-Yunusi (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2026)
The low learning outcomes and learning interest of third-grade students in Pendidikan Pancasila at MI Raudlatul Muta’alimin Wonokasian as indicated by teacher-centred instruction and limited media variation that leaves students passive and easily bored, necessitate innovation in more interactive learning media. This study aimed to analyze the effect of using Smart Box media on students’ learning outcomes and learning interest. A quasi-experimental method with a pretest–posttest control group design was employed, involving one experimental class (n = 31) using Smart Box and one control class (n = 22) using a wheel-of-fortune medium. The research instruments consisted of a learning achievement test (5 items) and a learning interest questionnaire (12 statements), while data were analyzed using independent-samples t-tests. The results showed that the mean posttest score of the experimental class (81.29) was higher than that of the control class (68.18), and the N-Gain of learning interest in the experimental class reached 53.00% (medium category), whereas the control class only achieved 29.96% (low category). These findings indicate that the use of Smart Box media has a significant effect on improving students’ learning outcomes and learning interest. The study underscores the importance of utilizing innovative and interactive learning media to promote more effective, meaningful, and learner-centred Pendidikan Pancasila instruction.